Liver Transplantation for Locally Advanced Hepatocellular Carcinoma - Kawamura, Norio; Taketomi, Akinobu (Digestive Disease Interventions, 2020)
Since the Milan criteria were accepted as the gold standard, liver transplantation has been widely performed as a curative treatment for early-stage hepatocellular carcinoma (HCC). The outcome of liver transplantation in early-stage HCC is excellent; however, the Milan criteria are strict, and therefore, only limited numbers of patients can benefit from liver transplantation. Many HCC patients are diagnosed at an advanced stage, which falls outside the Milan criteria, so it has been proposed over the last two decades that liver transplant surgeons should perform liver transplantation in locally advanced HCC, when presenting without recurrence. Several trials exploring the upper limits of liver transplantation have been performed, and extensive research on tumor biology has enabled the expansion of liver transplant indication for HCC. Simultaneously, locoregional therapy for advanced HCC was found to be an effective procedure when used to distinguish potentially transplantable patients. This treatment approach, known as a downstaging strategy, has been developed over the last two decades and became an essential treatment option for locally advanced HCC. In this article, the current strategies of liver transplantation for the treatment of locally advanced HCC are reviewed.
Keywords: hepatocellular carcinoma; liver transplantation; expanded criteria